Mid-infrared transmitting Ge-Sb-Se chalcogenide glass fibres: for potential use in medical diagnostics - Butterworth, Jessica Helen (2017)
This Project is aimed at developing and fabricating mid-infrared (MIR) transmitting germanium-antimony-selenium (Ge-Sb-Se) chalcogenide glass fibres for passive transmission in MIR sensing and as new high-purity low-loss optical fibres for active MIR supercontinuum generation (SCG). The work reported in this Thesis can be divided into three main categories: (i) a study of four Ge-Sb-Se glass compositions (atomic %): (Ge19Sb15Se66), (Ge20Sb10Se70), (Ge24Sb4Se72) and (Ge22Sb8Se70), in terms of their thermal properties, optical properties and cytotoxicity to match potential glass pairs for small-core step-index MIR SCG fibres; (ii) to develop and optimise methods of achieving high-purity chalcogenide glasses and (iii) a preliminary study of the structure of Ge-Sb-Se glasses along the stoichiometric tie-line x(GeSe2)-(1x)( Sb2Se3), to guide future selection of candidate glass pairs to draw to step-index fibre.